Dedicated and Reconfigurable Artificial Neurons and Synapses based on Two-Dimensional Materials for Efficient Neuromorphic Application - Chen, Danke; Yu, Peizhi; Li, Yuning; Shang, Jingwei; Wu, Haoyuan; Yao, Xuan; Tang, Xiaoqiu; Li, Chunlong; Zhu, Mingqiang; Gao, Chang; Sun, Jingye; Tian, He; et al. (Nano-Micro Letters, 2026)
Neuromorphic computing, a highly promising computational architecture, has provided an efficient solution to overcome the limitations of storage–compute separation and scaling constraints. The key to implementing this architecture lies in the development of artificial neurons and synapses as core neuromorphic components capable of biomimicry. Diverse libraries of two-dimensional (2D) materials with atomic-scale thickness and rich tunable physicochemical properties have risen to prominence in recent years. These unique properties meet the critical requirements of neuromorphic devices for ultralow power consumption, dynamic plasticity, and multifunctional integration, thereby facilitating breakthroughs in next-generation high-performance and versatile neuromorphic hardware systems. In this paper, recent advances in dedicated artificial neuron and synapse devices based on 2D materials are reviewed, with a focus on biomimetic models, physical mechanisms, and performance metrics. The discussion further extends to sophisticated switching strategies in reconfigurable components. Then, the systemic integration of neuromorphic devices is summarized, with particular focus on their functional roles in neural perception, neural networks, and logical operation tasks. Finally, a systematic analysis of the limitations at the device and system levels for artificial neurons and synapses is presented, charting a roadmap toward more efficient and multifunctional brain-like chips. Highlights: 1 This review summarizes recent advances in two-dimensional materials-based artificial neurons and synapses, focusing on their biomimetic models, physical mechanisms, and performance metrics, and further discusses sophisticated switching strategies in reconfigurable components. 2 The systemic integration of neuromorphic devices is presented, with particular emphasis on their functional roles in perception, neural networks, and logical operation tasks. 3 A holistic analysis of the challenge in developing artificial neuronal and synaptic devices and systems is presented, charting a roadmap toward more efficient and multifunctional brain-like chips.